Oxidative Deoximation of 3-Alkyl Substituted 2,6-Diphenyl Piperidin-4-one Oximes by Pyridinium Fluorochromate: A Kinetic Study - Tharini, K.; Jani Bai, T.S.; Lakshmi, M. (Asian Journal of Chemistry, 2010)
The oxidation of oximes of 2,6-diphenyl piperidin-4-one and various alkyl substituted 2,6-diphenyl piperidin-4-one by pyridinium fluorochromate (PFC) has been studied. The reaction follows first order each in [PFC] and [oxime]. The reactivity sequence observed is 3-H > 3-Me > 3-Et > 3,3-dime > 3-ipr which has been rationalized on the basis of steric crowding by the substituents.